(3eLehY aj GdcjejGAs - (3LGHQ Hf MjGf Hf YHO Gddg Gdchaj, CHh ehSi, J (B200 (3g` s
(3ChdgG (B:s
(3Chd GdehLhO efg bhdg ade JhMi GdMceGA HeKdg hEfge bO CcKQhG GdhUGjG Cf dGjhVY YfO ZjQ Cgdg hbO HYKJ Edjc HcJGH dh Xf GdChdhf HTF ef GdMceI s
(3BNQgG (B:s
(3abGd Cde CNHQc Cf eYde Pi ebQGW de jYdeg JQcjH GdCTjGA hJQcg ajgG eJLHQkG hGdMeO ddg QH GdYGdejf s
(3Vef eLehY , JQJjHgG (B: (3GdcJGH GdNGeSs
(3HgG fXGe GdJYbjHIs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B2 - (3U (B103s
(3cTa GdXfhf dMGLi NdjaI(B: (3L (B2 - (3U (B1450s
(3JHUQGJ GdCUd (B:s
(3GdfSNI fGbUI GdChd s
Keywords: (3GdcjejGA h GdWHjYjGJs